Post a New Question

intermediate algebra

posted by on .

rewrite with positive exponents. assume that even roots are of nonnegative quantities and thst all denominators are nonzero.
1 )-3
xy^3 )-3
everything times the negative power of 3 help please

  • intermediate algebra - ,

    (xy^3)^-3 = x^-3 * (y^3)^-3 = x^-3 * y^-9 = 1/x^3 * 1/y^9 = 1/(x^3 y^9)

    or, doing it the other way,

    (xy^3)^-3 = 1/(xy^3)^3 = 1/(x^3 y^9)

    Not sure what the initial 1)-3 is all about, but what I posted above should get you going.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question